What We Talk about When We Talk about Crime - Fleetwood, Jennifer (New York Review Books, 2024)
An examination of the increasingly public nature of crime and confession—from live-streamed offenses to Prince Andrew’s Newsnight interview—by a noted writer & lecturer in criminology. Over the past few decades, there has been a remarkable rise in the number of people who speak publicly about their experience of crime. These personal accounts used to be confined to private or professional settings—the police station, the courtroom, a helpline or in a counselor’s office—but today bookshops heave with autobiographies by prisoners, criminals, police, and lawyers; streaming platforms like Netflix and YouTube host hours of interviews with serial killers, death row residents, vigilantes, and gang members; true-crime podcasts like Criminal often feature episodes focusing entirely on one person’s narrative; and some offenders even live-stream their crimes. In this fascinating new book, British criminologist Jennifer Fleetwood compellingly examines seven high-profile “crimes” which are known to us via a public, first-person account to try to make sense of the social, political, and cultural consequences that this confessional impulse has on our lives. From Howard Marks’s autobiography Mr. Nice to Shamima Begum’s 2019 Times interview; from the documentary The Real Mo Farah to Prince Andrew’s disastrous Newsnight interview; from Chanel Miller’s victim impact statement to episodes of Criminal and Myra Hindley’s prison letters, Fleetwood invites us to think differently about the abundance of personal stories about crime that circulate in public life.